A.G. van Aarde en historiese Jesus-navorsing - Merwe, Gerrit-Daan van der (HTS teologiese studies, 2015)
A.G. van Aarde and historical Jesus research. A.G. van Aarde’s contribution to historical Jesus research is mainly expressed in his book Fatherless in Galilee: Jesus as Child of God. The book was the result of five years of Jesus research. Van Aarde is an ordained minister of the Netherdutch Reformed Church of Africa (NRCA). Since the book’s publication in 2001, the NRCA has experienced an immense dispute regarding the book in particular but also regarding the subject of historical Jesus research in general. This dispute has publicly escalated since 2010. It has often centred on Van Aarde’s notion of Jesus’ fatherlessness. This article will focus on said book in order to ascertain what is meant by the concept ‘the fatherless Jesus’. This is done to illustrate that Van Aarde’s research, as it converges in the scrutinised publication, remains of relevance to the NRCA.